An audit of traumatic brain injury (TBI) in a busy developing-world trauma service exposes a significant deficit in resources available to manage severe TBI - Jerome, E; Laing, GL; Bruce, JL; Sartorius, B; Brysiewicz, P; Clarke, DL (Health and Medical Publishing Group, 2017)
Background: Traumatic brain injury (TBI) affects large numbers of patients, both adults and children, and significant resources are needed to manage it. Objective: To determine the burden of TBI and the adequacy of available resources to manage in the Pietermaritzburg Metropolitan Trauma Service (PMTS). Methods: All patients with a TBI were identified from the hybrid electronic medical registry at Grey’s and Edendale hospitals in Pietermaritzburg (PMB), KwaZulu-Natal, South Africa. Patients were classified according to severity of head injury and age. We defined mild TBI as Glasgow coma scale (GCS) 13 - 15, moderate as GCS 9 - 12, and severe as GCS ≤8, in accordance with international standards. We divided the cohort according to ages 0 - 5 years, 6 - 10 years, >10 - 17 years and adults (>17 years). Results: From January 2012 to December 2014, 3 301 patients were treated for TBI in PMB. The mean age was 27.4 (standard deviation 14.4) years. There were 2 632 males and 564 females. There were 2 540 mild, 326 moderate, and 329 severe TBI admissions during the period under review. A total of 139 (4.2%) patients died. A total of 242 (7.3%) patients were admitted to the intensive care unit (ICU), of whom 137 (57.0%) had a GCS of ≤9. Only 27.0% of patients with a GCS of ≤9 were admitted to the ICU. Conclusion: There is a significant burden of TBI managed by the PMTS. Critical care resources available to manage patients with TBI are inadequate.